PELAKSANAAN PENETAPAN MAHAR PERKAWINAN DI DESA BATURIJAL HILIR KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Dito Prananda; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Mahar is a mandatory gift given and declared by prospective husbands to prospective wives in thesighat marriage contract which is a sign of their agreement and willingness to live as husband and wife.While the dowry law of the scholars agreed that the dowry is one of the legal requirements of marriage andmay not enter into an agreement to leave it. In terms of the level of dowry there are no provisions in theQur'an and the Sunnah, but the Prophet advocates for his people to facilitate dowry. The problems of thisstudy are how the marital determination procession in the village of Baturijal Hilir Peranap Subdistrict, andwhat causes the existence of levels in the determination of marriages in the village of Baturijal Hilir. Thisstudy aims to determine the process of determining the dowry in marriage in the village of Baturijal Hilir, tofind out the implications (impacts) on the people of Baturijal Hulu village and to find out a review of Islamiclaw on the establishment of dowry in marriage in the village. This research is in the form of field research,which takes place in the village of Baturijal Hulu.The methods in this study are observation, interviews, and questionnaires. The subjects of this studywere people who had done marriages and community leaders in the village of Baturijal Hulu, PeranapDistrict, Indragiri Hulu Regency. The object of this research is the determination of dowry in marriage andits implications for society. The population in this study were all communities in the village of Baturijal HuluPeranap Subdistrict Indragiri Hulu Regency who had canceled 12 marriages and who had married as manyas 20 people with a sample of 6 people canceling their marriages and 10 marriages who married. withPurposive Sampling techniques.Once collected, the authors analyze the data through qualitative analysis, while the methods used aredeductive, inductive and analytical descriptive methods. The people of Baturijal Hulu Village, PeranapSubdistrict, Indragiri Hulu Regency, in setting dowry are based on their education level and economic level,the higher the education level of the woman the greater the dowry that is asked in her marriage later.Likewise with middle and upper economic families, they also ask for a high dowry. Whereas theeconomically disadvantaged people only ask for a modest dowry that is like a set of prayer tools, with thedetermination of the dowry problem many people are burdened and find it difficult because of the highdowry, so many cannot fulfill these requirements. The determination of the dowry has a negative andpositive impact on the community, because of the large amount of dowry determined. The establishment ofdowry in the village of Baturijal Hulu is contrary to Islamic law, because according to good dowry Islam isa light and not burdensome one, even an iron ring or memorization or teaching the Qur'an is a better dowry.In the determination of dowry must pay attention to the capabilities of the male side.Keywords: Mahar, Marriage, Baturijal Hilir.